Comorbidity classes and associated impairment, demographics and 9/11-exposures in 8, 236 children and adolescents. (January 2018) - Geronazzo-Alman, Lupo; Guffanti, Guia; Eisenberg, Ruth; Fan, Bin; Musa, George J.; Wicks, Judith; Bresnahan, Michaeline; Duarte, Cristiane S.; Hoven, Christina
Abstract: The extensive comorbidity of psychiatric disorders in children and adolescents leads to clinical heterogeneity, and is an often-overlooked issue in etiopathogenic and treatment studies in developmental psychopathology. In a representative sample (N=8236) of New York City public school students assessed six months after 9/11, latent class analysis was applied to 48 symptoms across seven disorders: posttraumatic stress, agoraphobia, separation anxiety, panic disorder, generalized anxiety (GAD), major depression (MDD) and conduct disorder (CD). Our objective was to identify classes defined by homogenous symptom profiles, and to examine the association between class membership and gender, age, race, different types of exposure to 9/11, and impairment. Eight homogenous comorbidity patterns were identified, including four severe disturbance classes: a multimorbid internalizing class (INT), a class with a high probability of CD, MDD, and GAD symptoms (Distress/EXT), a non-comorbid externalizing class, and a non-comorbid MDD class. Demographic and 9/11-related exposures showed some degree of specificity in their association with severe symptom profiles. Impairment was particularly high in the INT and Distress/EXT classes. A better characterization of phenomic data, that takes comorbidity into account, is essential to understand etiopathogenic processes, and to move psychiatric research forward towards personalized medicine. The high probability of endorsing symptoms of multiple disorders in the INT and Distress/EXT classes supports the use of treatments focusing on multimorbidity. Clinical trials should evaluate the effectiveness of disorder-specific versus transdiagnostic interventions. The association between class membership and demographic and exposure variables suggests that interventions may be improved by considering specific predictors of class membership. Highlights: We identified distinct symptom profiles in youth, and their association with demographics, 9/11 exposures and impairment. Eight comorbidity patterns were identified, including 4 severe disturbance classes. Demographic, 9/11-related experiences, and impairment showed specific associations with severe symptom profiles. Interventions may be improved by considering comorbidity patterns and their predictors.